Tomás Mejía - Mejía, Tomás (Cinzontle, 2024)
The multifaceted plastic artist Tomás Martínez Mejía was born on March 7, 1969 in Villahermosa, Tabasco, Mexico. In 1991, he began studying fine arts at the José Gorostiza House of Arts, taking different courses and diplomas that enriched his career. In addition, he stood out as a teacher teaching different painting, sculpture and engraving courses throughout his career and due to his great artistic talent he participated as a jury in different competitions and artistic disciplines both in Tabasco and nationally.